HUBUNGAN ANTARA FORWARD HEAD POSTURE DENGAN KESEIMBANGAN STATIS PADA LANSIA DI KELURAHAN UNTIA KOTA MAKASSAR - Himmatul Aliyah; Rini, Ita; Salki Sadmita (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Humans will inevitably experience stages of the aging process which will result in functional and anatomical changes in organs such as a decrease in the musculoskeletal system which if there is a decrease in the system will affect changes in posture, one of which is forward head posture. This posture condition will cause difficulty in controlling balance. This study aims to determine the relationship between forward head posture and static balance in the elderly in Untia Village, Makassar City. This research is included in the type of quantitative research using a cross-sectional approach. Respondents of this study were elderly people aged over 60 years as many as 67 elderly people who met the exclusion and inclusion criteria. The normality test used is Kolmogorov Smirnov which shows the significance value (p) of Kolmogorov Smirnov of 0.000 which means that the data is not normally distributed (p <0.05). Furthermore, a non-parametric correlation test was carried out, namely Spearman's rho correlation and obtained variable results of 0.001 (p <0.05) which means that the two variables have a significant (real) relationship, namely between forward head posture and static balance with data obtained by researchers showing 46 of 67 respondents had FHP conditions and 38 of 67 elderly people experienced low stability. The results of the study showed that there was a relationship between forward head posture and static balance in the elderly in Untia Village, Makassar City. Keywords: Elderly, Forward Head Posture, Static Balance.